A contratação de aprendizes: o reflexo da aprendizagem de adolescentes na cultura organizacional - Silva, Nicéia Luzia Selete (2008)
The primary main of this study is to assess the hiring and teenager learning labour process in the companies organizational culture. It unfolds in specific objectives to achieve and intend to examine specific and relevant legislation that controls teenager profession learning; study the learning and the organizational culture and their interconnections. Identify cultural characteristics and organizational learning from the companies, with learning shares, showing the greater emphasis elements; and; assess the learner compulsory presence in the organizations culture studied. For that reason, documentary information was collected from the Teenager Learner Project, which applies technical training course and forwards the participants to the learning practice in the companies. This Project is developed by Universidade Paranaense UNIPAR in partnership with Guarda Mirim de Umuarama, Ministério Publico do Trabalho and Ministério do Trabalho. Beyond the documents evaluation and laws, the investigation got an interview with the Guarda Mirim coordination, companies representatives, Ministerio do Trabalho and Ministerio Publico do Trabalho representatives, with the teenagers and theoretical course monitors. Still it was applied one questionnaire to the teenagers and to the contractors companies representatives. The discussion and analysis of concepts like organizational learning, vocational learning, learning management, organizational culture, culture management, and knowledge are predominant in this study. On that way, scientific reasoning of the learning process and cultural process in the organizations are presented and it shows like they are linked. Teenager learning into the business space is a new subject that came from the federal law 10097/2000. The organizations that follow that normative hire below 18 years old learners, without experience. The questions that this work proposes are linked to the kind of influence that this companies can have in their work groups, their culture from this new human element in their environment. With this research it was noted that despite from having perception of the learners use like a cheap labour, their collaboration in the company is significant into the work group, and, gradually, won these organizations trust